2016
DOI: 10.5051/jpis.2016.46.2.72
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective long-term analysis of bone level changes after horizontal alveolar crest reconstruction with autologous bone grafts harvested from the posterior region of the mandible

Abstract: PurposeThe goal of this study was to evaluate the long-term success of horizontal alveolar crest augmentation of the retromolar region of the mandible with particulated bone, as well as factors affecting subsequent peri-implant bone loss.MethodsA total of 109 patients (68 female, 41 male) suffering from alveolar ridge deficiencies of the maxilla and mandible were included in this study. All patients were treated with particulated retromolar bone grafts from the mandible prior to the insertion of endosseous den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The survival rate was 97s%. They concluded that implants placed in augmented bone gave similar results to implants inserted in nonaugmented regions [ 8 ]. Degidi et al [ 9 ] reported a higher success rate of approximately 97.7s% for 133 short dental implants that were immediately loaded.…”
Section: Introductionmentioning
confidence: 99%
“…The survival rate was 97s%. They concluded that implants placed in augmented bone gave similar results to implants inserted in nonaugmented regions [ 8 ]. Degidi et al [ 9 ] reported a higher success rate of approximately 97.7s% for 133 short dental implants that were immediately loaded.…”
Section: Introductionmentioning
confidence: 99%
“…Bone graft blocks from the mandibular ramus have been widely used in small bone reconstructions prior to the installation of dental implants (Voss et al, 2016), which have shown high success rates of implants installed in grafted sites (Clementini et al, 2011). Peñarrocha-Oltra et al (2014, in a study conducted on 37 patients, showed a 91 % success rate of dental implants in sites augmented with bone from the mandibular ramus.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 11 articles analyzed, 9 were prospective and 2 were retrospective. In all the studies, implant installation was delayed; i.e., healing time was expected after graft placement, which was 3 to 5 months in the study by Soehardi et al (2009), 4 months in the works by Happe (2007), Cordaro et al (2011) and Streckbein et al (2014), 4 to 5 months in the studies by Restoy-Lozano et al (2015) and Sakkas et al (2016); 5 months in the work by Singh et al (2013), and 4 to 6 months in the study by Voss et al (2016). On the other hand, in the works by Prousaeffs et al (2002) and Greenberg et al (2012), the expected time was 6 months, whereas in the work by Peñarrocha-Oltra et al (2014) it was 7 months.…”
Section: Study Selectionmentioning
confidence: 95%